Frailty assessment for COVID-19 follow-up: a prospective cohort study. Issue 1 (22nd April 2022) - Müller, Ilena; Mancinetti, Marco; Renner, Anja; Bridevaux, Pierre-Olivier; Brutsche, Martin H; Clarenbach, Christian; Garzoni, Christian; Lenoir, Alexandra; Naccini, Bruno; Ott, Sebastian; Piquilloud, Lise; Prella, Maura; et al.
Abstract : Background: The Clinical Frailty Scale (CFS) is increasingly used for clinical decision making in acute care but little is known about frailty after COVID-19. Objectives: To investigate frailty and the CFS for post-COVID-19 follow-up. Methods: This prospective multicentre cohort study included COVID-19 survivors aged ≥50 years presenting for a follow-up visit ≥3 months after the acute illness. Nine centres retrospectively collected pre-COVID-19 CFS and prospectively CFS at follow-up. Three centres completed the Frailty Index (FI), the short physical performance battery (SPPB), 30 s sit-to-stand test and handgrip strength measurements. Mixed effect logistic regression models accounting for repeated measurements and potential confounders were used to investigate factors associated with post-COVID-19 CFS. Criterion and construct validity were determined by correlating the CFS to other concurrently assessed frailty measurements and measures of respiratory impairment, respectively. Results: Of the 288 participants 65% were men, mean (SD) age was 65.1 (9) years. Median (IQR) CFS at follow-up was 3 (2–3), 21% were vulnerable or frail (CFS ≥4). The CFS was responsive to change, correlated with the FI (r=0.69, p<0.001), the SPPB score (r=−0.48, p<0.001) (criterion validity) and with the St George's Respiratory Questionnaire score (r=0.59, p<0.001), forced vital capacity %-predicted (r=−0.25, p<0.001), 6 min walk distance (r=−0.39, p<0.001) and modified Medical Research Council (mMRC) (r=0.59, p<0.001). Dyspnoea was significantly associated with a higher odds for vulnerability/frailty (per one mMRC adjusted OR 2.01 (95% CI 1.13 to 3.58), p=0.02). Conclusions: The CFS significantly increases with COVID-19, and dyspnoea is an important risk factor for post-COVID-19 frailty and should be addressed thoroughly.